Adobe Creative Suite 5 Web premium how-tos 100 essential techniques - Karlins, David; Safari eBooks (Berkeley, Calif. : AdobePress : Peachpit, 2011)
"'Adobe Creative Suite CS5 Web Premium How-Tos: Essential Techniques' is a concise, economical, current, and informed guide to the key techniques for creating inviting and accessible Web sites using Adobe Creative Suite CS5. Readers choose the How-Tos guide when they want immediate access to just what they need to know to get results. This book shows readers the Dreamweaver CS5 features they need to manage Web sites; design page layout with CSS styles; and generate menu bars, tabbed panels, tooltips, datasets, and forms with validation scripts. It gives readers the Photoshop CS5 skills to prepare photos and thumbnails for the Web. It teaches Illustrator CS5 techniques to create Web banners, navigations icons, and scalable graphic elements. It shows how to create scrollbars and buttons in Flash Catalyst CS5. Readers can learn to generate animation in Flash Professional CS5, and they can discover ways to integrate Dreamweaver, Photoshop, Illustrator, and Flash to create cutting-edge Web sites with custom video players, animation, and interactivity"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Adobe Creative Suite; Dreamweaver (Computer file); Computer graphics; Computer animation; Digital video; Electronic books